Exam DP-900 Microsoft Azure Data Fundamentals (Video) - Sorensen, Chris (Microsoft Press, 2021)
4+ Hours of Video Instruction Prepare for Microsoft Exam DP-900 and demonstrate your knowledge of fundamental data concepts and Microsoft Azure data services. Description This Exam DP-900: Microsoft Azure Data Fundamentals video is designed to help you begin to work with data in the cloud. This video focuses on the skills measured by the exam objectives, as updated by Microsoft in April 2021. Describe core data concepts Describe how to work with relational data on Azure Describe how to work with non-relational data on Azure Describe an analytics workload on Azure Using his years of experience working with data and teaching data best practices to a variety of learners, Microsoft Certified Trainer Chris Sorensen explains core concepts related to working with data in Azure. In his engaging style grounded in real-world scenarios, Chris gives you insights to relational and non-relational data, different types of workloads, and analytical best practices. With Chris as your guide, you are well-equipped to successfully attempt the DP-900 exam and advance in your career as a data engineer or database administrator. About the Instructor Chris Sorensen, CPA, CGA, is the Founder and President of Iteration Insights, a tech-enabled data analytics solutions provider based in Calgary, Alberta. He is a Microsoft Certified Data Analyst Associate and Microsoft Certified Trainer with a combined 20+ years of industry and teaching experience. In his career, he has led numerous Analytics projects in more than 15 industries across small to enterprise-sized organizations. As an adjunct instructor of the Business Intelligence program at SAIT, he plays a significant role in shaping new talent in Calgary's emerging tech sector. Following his lifelong learning approach, Chris also coordinates both Power Platform and Azure Analytics User Groups, providing a space dedicated to knowledge-sharing and growing Alberta's tech community. His favourite hashtag is #neverstoplearning. Skill Level Beginner to Intermediate Who Should Take This Course Certification candidates preparing for exam DP-900 Microsoft Azure Data Fundamentals Analysts or admins beginning to work with data in the cloud Course Requirements Foundational knowledge of core data concepts About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal techn ...